2004
DOI: 10.1242/dev.01429
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest stem cells undergo multilineage differentiation in developing peripheral nerves to generate endoneurial fibroblasts in addition to Schwann cells

Abstract: Neural crest stem cells (NCSCs) persist in peripheral nerves throughout late gestation but their function is unknown. Current models of nerve development only consider the generation of Schwann cells from neural crest, but the presence of NCSCs raises the possibility of multilineage differentiation. We performed Crerecombinase fate mapping to determine which nerve cells are neural crest derived. Endoneurial fibroblasts, in addition to myelinating and non-myelinating Schwann cells, were neural crest derived, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
254
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(281 citation statements)
references
References 41 publications
19
254
0
Order By: Relevance
“…1D). In the limbs, neural crest-derived Schwann cells (D'Amico-Martel and Noden, 1983) were GFPpositive, whereas the surrounding mesoderm-derived perineurium (Joseph et al, 2004) was not ( Fig. 1E).…”
Section: Research Articlementioning
confidence: 99%
“…1D). In the limbs, neural crest-derived Schwann cells (D'Amico-Martel and Noden, 1983) were GFPpositive, whereas the surrounding mesoderm-derived perineurium (Joseph et al, 2004) was not ( Fig. 1E).…”
Section: Research Articlementioning
confidence: 99%
“…They generate immature Schwann cells, endoneurial fibroblasts of fetal nerves as well as melanocytes, parasympathetic neurons and odontoblasts (Joseph et al, 2004;Adameyko et al, 2009;Dyachuk et al, 2014;Espinosa-Medina et al, 2014;Kaukua et al, 2014). Schwann cell progenitors give rise to immature Schwann cells around E16 (Jessen et al, 2015).…”
Section: Schwann Cell Precursorsmentioning
confidence: 99%
“…Recently, using Cre recombinase-mediated fate mapping, it was shown that the small population of endoneurial fibroblasts present in P11 mice sciatic nerves were derived from cells present in E12 embryonic nerves (Joseph et al, 2004). The large majority of the cells in the E12 nerves are SCPs, i.e.…”
Section: Schwann Cell Precursor Differentiationmentioning
confidence: 99%